The Pattern and Frequency of Acrylic Stock Teeth Usage in Prosthodontic Patients of a Teaching Hospital of Punjab - Qamar, Khezran; Ijaz , Yusra; Khan, Mahira; Bin Yousaf, Abdullah; Nasir , Muhammad Uzair; Hamid, Tayyaba; Naeem, Sajid (Indus Journal of Bioscience Research, 2025)
Back ground: Acrylic stock teeth are widely used for replacement of partial or complete loss of teeth in denture patients because of cost effectivity, aesthetics and easy modification. Objective: To find out the frequency of acrylic stock teeth usage in complete and partial dentures (RPDs) and determine the association of usage pattern of stock teeth in RPDs within age groups and gender. Methodology: The Secondary data collected from patients’ laboratory work authorization registers between year 2023 to 2024 from prosthodontic laboratory. The records of patients attending for partial or complete loss of teeth and need replacement via complete and partial dentures were selected. The parameters of the study were patients’ age groups, frequency and percentages of stock teeth used with respect to gender and types of dentures. Results: A total of 1,306 acrylic dentures; 54.1% sets of complete dentures and 45.9% partial dentures were made. 56.0% males and 52.0% female patients received complete dentures whereas removable partial dentures were fabricated for 44.0% males and 48.0% females. Maximum number of stock teeth used in age group <50 years were in anterior maxilla; 91.4%, whereas in >50 years 87.8% teeth used in posterior maxilla. Maximum male had teeth replacements in posterior mandible 76.9% and females had in anterior maxillary 84.6%. The association of stock teeth with respect to age groups and gender was statistically significant p<0.05. Conclusion: In our region, partial and complete edentulism are prevalent, with a high demand for tooth replacements. Notably younger individuals often require replacement of anterior maxillary and mandibular teeth, whereas older individuals tend to need more posterior teeth replacements in both jaws.